1997
DOI: 10.1159/000139536
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Attenuates Mechanical and Metabolic Derangements Induced by Palmitoyl-L-Carnitine in the Isolated Perfused Rat Heart

Abstract: The effect of lidocaine on the palmitoyl-L-carnitine (PAL-CAR)-induced mechanical and metabolic derangements was studied in Langendorff rat hearts, perfused aerobically at a constant flow rate and paced electrically. PALCAR (5 µmol/l) increased the left ventricular end-diastolic pressure, decreased the left ventricular developed pressure (i.e., mechanical dysfunction), and decreased the tissue levels of adenosine triphosphate and creatine phosphate (i.e., metabolic change). These mechanical and metabolic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The content of long-chain acyl carnitines (including PC) increases in myocytes during hypoxia (DaTorre et al, 1991), and these molecules are reported to accumulate in sarcolemmal membranes (Knabb et al, 1986). Although the concentration of PC in ischemic myocardial cells has not been reported to our knowledge and the effects of endogenously produced and exogenously applied PC may be different, the concentration of 4 M PC used in this study is similar to concentrations used in previous studies (Mészà ros and Pappano, 1990;Sato et al, 1992;Wu and Corr, 1992;Shen and Pappano, 1995;Arakawa et al, 1997;Arakawa and Hara, 1999;Netticadan et al, 1999;Maruyama et al, 2000), and the effects of an exogenous application of 4 M PC in this study are similar in magnitude to the effects of brief ischemia associated with a 4-to 5-fold elevation of long-chain acyl carnitine content in the heart (DaTorre et al, 1991). Thus, the results of the present study suggest that a pathologically enhanced, PC-induced late I Na may be a contributor to ischemia-induced dysfunction.…”
Section: Discussionsupporting
confidence: 59%
“…The content of long-chain acyl carnitines (including PC) increases in myocytes during hypoxia (DaTorre et al, 1991), and these molecules are reported to accumulate in sarcolemmal membranes (Knabb et al, 1986). Although the concentration of PC in ischemic myocardial cells has not been reported to our knowledge and the effects of endogenously produced and exogenously applied PC may be different, the concentration of 4 M PC used in this study is similar to concentrations used in previous studies (Mészà ros and Pappano, 1990;Sato et al, 1992;Wu and Corr, 1992;Shen and Pappano, 1995;Arakawa et al, 1997;Arakawa and Hara, 1999;Netticadan et al, 1999;Maruyama et al, 2000), and the effects of an exogenous application of 4 M PC in this study are similar in magnitude to the effects of brief ischemia associated with a 4-to 5-fold elevation of long-chain acyl carnitine content in the heart (DaTorre et al, 1991). Thus, the results of the present study suggest that a pathologically enhanced, PC-induced late I Na may be a contributor to ischemia-induced dysfunction.…”
Section: Discussionsupporting
confidence: 59%
“…Long-chain acylcarnitines are regarded as one of the important factors in producing irreversible damage in the ischemic heart [6,7], and therefore several studies have addressed the actions of substances that protect the myocardium from damage induced by long-chain acylcarnitine [10,[15][16][17][18]. We have shown that lidocaine [15], dilazep [16,17] and diltiazem [10] attenuate the PALCAR-induced mechanical and metabolic derangements in the isolated perfused heart.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that lidocaine [15], dilazep [16,17] and diltiazem [10] attenuate the PALCAR-induced mechanical and metabolic derangements in the isolated perfused heart. Kang and Leaf [18] have reported that free polyunsaturated fatty acids attenuate arrhythmia induced by PAL- CAR in cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations